الأنظمة الجمركية الاقتصادي كألية لترقية الصادرات دراسة حالة إدارة الجمارك الوادي (2017/2023) - هنية, قديري; أنفال, قادري (جامعة الوادي - University of Eloued, 2023)
" هدفت الدراسة إلى تحديد دور الأنظمة الاقتصادية الجمركية في ترقية الصادرات باستعمال الاسلوب الوصفي التحليلي، أما الدراسة الميدانية فقد تمت في مديرية الجمارك الجزائرية بالوادي حيث مت إجراء مقابلة مع رئيس مفتشية ومراقبة العمليات التجارية ومحاولة دراسة واقع المرافقة والدعم الذي تقدمه الدولة من من خلال الهيئات التي وضعتها في متناول المؤسسات الاقتصادية. ومن خلال دراستنا هذه حاولنا تحليل واقع التجارة الخارجية وخاصة الصادرات،وبناءا على ماسبق تم الخروج بأهم النتائج التالية إذ أن للأنظمة الاقتصادية الجمركية دور هام في ترقية الصادرات تمثل تسهيلات تقدم للمؤسسات لتحفيزهم على الانتاج و التصدير.كما تم التوصل أن الأنظمة تمنح تخفيضات أو إعفاء أو إيقاف البضائع من الرسوم و الحقوق الجمركية مما يقلل من مختلف التكاليف مما يضمن السرعة في آداء المهام في وقتها إد يتم استنتاج أن الجمارك تلعب دور مهم في حماية الاقتصاد الوطني من العقبات التي تواجهه.""The study aimed to determine the role of customs economic systems in promoting exports using the descriptive analytical method. As for the field study, it was conducted in the Algerian Customs Directorate in El-oued, where an interview was conducted with the head of the Inspectorate and Control of Commercial Operations and an attempt to study the reality of the accompaniment and support provided by the state through the bodies that placed within the reach of economic institutions .Through our study, we tried to analyze the reality of foreign trade, especially exports, and based on the foregoing, the following most important results were obtained, as the customs economic systems have an important role in promoting exports, as they represent facilities provided to institutions to stimulate them to produce and export. It was also concluded that the systems grant discounts or exemptions Or stopping goods from duties and customs rights, which reduces the various costs, which ensures speed in performing tasks in a timely manner. It is concluded that customs play an important role in protecting the national economy from the obstacles it faces."
Keywords: أنظمة جمركية ,جمارك ,تصدير,مؤسسات اقتصادية ,تجارة خارجية; customs regulations, customs, export, economic institutions, foreign trade.